Forensic Histopathological Approach to Electrocution - Al-Hadithi, Raji Hussein Mohammad; Al-Khateeb, Nabeel Ghazi Hashim; Abdullah, Muthana Abdul- Jabar (Journal of the Faculty of Medicine Baghdad, 2008)
Background: Few Studies had been done on the role of histopathology in the medico-legal diagnosis of Electrocution even abroad.Aim of the study: To determine the main histopathlogical features in cases of electrocution especially at the entry site of the electrical current which help in the diagnosis of those cases.Methods: A full medico-legal autopsy had been done on 64 cadavers of persons died as a result of electrocution chosen randomly out of a total number of 144 cases of electrocutionduring the year 2005 in the medico-legal institute of Baghdad including histopathological examination by ordinary method of different specimens from those cadavers at histopathologydepartment of the mentioned institute to reach the aim of this study.Results: Electrocution constituted only 1.4% of all causes of death during the year 2005 in the medico-legal institute of Baghdad. Males were more than females in a ratio of 2:1. The mostaffected age group was 30- 39 years old. In 62% of the case the entry of the current was with no exit. In 46.9% of the cases the entry site was in the form of charged centre surrounded bygray elevated area and took other shapes in the rest of the cases. Microvesicural formation was the commonest histopathological finding in the skin. Pulmonary edema was the commonest histopathological finding in the lung.Conclusions: Although they are non specific, histopatological features could help the forensic pathologist in the medico-legal diagnosis of electrocution in addition with other findingsespecially in cases with less typical gross features or with incomplete information about the case, in addition to other conclusions of the study.